"Com-Passion": Journeying to Joy by "Suffering-with" Your Patients. (May 2022) - Ashour, Monica
Catholic medical professionals whose sacred mission of journeying with patients "with suffering" will be challenged regarding the truth of soteriology (how we are saved) with their work with patients. Using St. John Paul's Theology of the Body and "On the Christian Meaning of Human Suffering, " this essay gives a profound understanding of the coredemption in which healthcare professionals can participate.